1998
DOI: 10.1021/jp973113m
|View full text |Cite
|
Sign up to set email alerts
|

Photoeffects on the Reduction of Carbon Tetrachloride by Zero-Valent Iron

Abstract: While reduction of chlorinated hydrocarbons by zero-valent iron in water is strongly influenced by the oxide layer at the metal−water interface, the role of the oxide in the dechlorination mechanism has not been fully characterized. In this paper, we investigate the semiconducting properties of the oxide layer on granular iron and show how the electronic properties of the oxide affect electron transfer to aqueous CCl4. Specifically, we determine whether conduction-band electrons contribute to the reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 53 publications
1
110
2
Order By: Relevance
“…Zero-valent metals have been the focus of much recent attention in the environmental 27 community because they offer great promise in treating contaminated groundwater through their 28 ability to promote abiotic reductive dehalogenation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Nevertheless, many basic questions 29 about the mechanism of these reactions remain unanswered.…”
mentioning
confidence: 99%
“…Zero-valent metals have been the focus of much recent attention in the environmental 27 community because they offer great promise in treating contaminated groundwater through their 28 ability to promote abiotic reductive dehalogenation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Nevertheless, many basic questions 29 about the mechanism of these reactions remain unanswered.…”
mentioning
confidence: 99%
“…• was confirmed by d8-isopropanol experiments, and radical trapping experiments using dimethylbutene (DMB) respectively (Danielsen and Hayes 2004;Elsner et al 2004 (Balko and Tratnyek 1998). However studies on goethite/Fe 2+ systems have shown that this does not occur (Elsner et al 2004), and we do not consider cleavage of 2 C-Cl bonds to be likely.…”
Section: Effect Of Ph and H Donormentioning
confidence: 64%
“…With Fe_fresh-HCl after reaction, also peaks due to lepidocrocite ( -FeO(OH)) are observed ( Figure 1 [59,67].…”
Section: Physicochemical Characterization Of the Solid Fractionmentioning
confidence: 99%